PENINGKATAN KUALITAS HIDUP PASIEN HEMODIALISA DITINJAU DARI PERILAKU CARING PERAWAT DI RSUD dr. SOETOMO SURABAYA - Nikmatul Fadilah; Dyah Wijayanti; Tumini Tumini (Jurnal Kesehatan Manarang, 2016)
Patients with chronic renal failure who undergoing hemodialysis decreased vitality, physical and psychological function that caused of decreased quality of life. The effect of caring to patient are improved relations of mutual trust, increase physical healing andsafety, have more energy, lower maintenance costs and create more comfortable feeling. The purpose of this study was to analyze the relationship between caring behaviors with quality of life. This study was analytic cross sectional. The sample was 60 patients in Hemodialysis Unit RSU Dr.Soetomo Surabaya, that was taken by purposive sampling. Independent variable wascaring behaviors, and dependent variable wasquality of life. Data were collected using 25-Caring Dimension Inventory (CDI 25) questionnaire and modifications Kidney Dissease Quality of Life Short Form. Data were analysis using Spearman's Rho test with α 0.05. The results showed that a good caring behavior (48.3%) and excellent (51.7%). The quality of life was moderate (83.3%). Spearman's rho test showed that the caring behavior did not significantly influence the quality of life with p value 0.229. The achievement of good judgment by patients need to be maintained and enhanced so that it will create a positive image of nurses from the public. Quality of life who have reached the moderate level needs to be improved, with a joint effort between the patient, family, and health workers. Improved quality of life, especially physical and psychological dimensions so that the patient will achieve adaptive coping strategies, while supported by families and health workers, especially nurses as part of the environmental and social dimensions of the patient.